Influence of Epoch Length and Recording Site on the Relationship Between Tri-Axial Accelerometry-Derived Physical Activity Levels and Structural, Functional, and Hemodynamic Properties of Central and Peripheral Arteries - Gómez-García, Mariana; Torrado, Juan; Bia, Daniel; Zócalo, Yanina (Frontiers in Sports and Active Living, 2022)
Background: It remains to be established to what extent physical activity (PA) levels among individuals are independently associated with deviations from the “optimal” state of the arterial system. Accelerometers have been proposed as means to obtain reliable, objective and more comprehensive data of PA. Decisions at the time of data collection/processing could influence the association between accelerometry-derived indexes and arterial properties. Objectives: (i) to identify to what extent the strength of association between arterial properties and accelerometer-derived indexes depend on the recording site and/or the epoch length; (ii) to determine whether some arterial characteristics (hemodynamic vs. structural vs. functional) or regions (elastic vs. transitional vs. muscular arteries; central vs. peripheral) have higher levels of association with accelerometry-derived indexes. Methods: PA, cardiovascular risk factors (CRFs) and cardiovascular properties were evaluated in 60 volunteers (general population; age: 23-62 y; females: 43%). PA was measured daily during seven days (free-living situation; triaxial-accelerometers ActiGraph-GT3X+; hip and wrist; ´Worn-to-wrist´ option); raw data was converted at epoch lengths of 1, 5, 10, 30 and 60-s. PA-related energy expenditure, daily time in moderate-to-vigorous PA, steps/minute and counts-per-minute for vector magnitude, were calculated. Cardiovascular evaluation included: hemodynamic (central and peripheral pressure), structural (diameters, intima-media thickness) and functional (local and regional stiffness) parameters of carotids, femoral, and brachial arteries, and carotid-femoral and carotid-radial pathways. Arterial z-scores were obtained using age-related equations derived from healthy participants not-exposed to CRFs (n=1688; age: 2-84 y; females: 51.2%) to evaluate at which degree each parameter deviates from the ´optimal´ value. Results: In general, hip recordings outperformed those obtained on the wrist regarding the strength of association with arterial parameters. Accelerometer-derived indexes and their association with arterial properties vary depending on the recording site and epoch length. PA indexes are stronger associated with functional (local) than structural variables and with central than peripheral arteries. Conclusions: Regardless of the PA index, there were independent associations with central arteries characteristics, which reinforces that these territories would be the most related to PA levels. Differences in data acquisition and processing could lead to differences in conclusions when addressing the association between accelerometer-derived indexes and the cardiovascular system.